Enhancing EFL Reading Comprehension through the Jigsaw Technique: A Systematic Review - Nuranisa Panggabean; Seful Bahri (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2026)
Numerous studies have examined reading comprehension in English as a Foreign Language (EFL) classroom; however, inconsistencies remain regarding the effectiveness of cooperative learning strategies, particularly in fostering social interaction and individual responsibility. Although the jigsaw technique has frequently been recommended, few studies have explored how its core aspects influence reading outcomes. This study aims to investigate, through a systematic literature review using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework, how the application of the jigsaw technique improves reading comprehension in EFL classrooms. A total of 24 relevant articles published between 2016 and 2025 were selected and systematically analyzed. The findings reveal two main aspects of the jigsaw technique’s implementation in the classroom: (1) building new knowledge through discussion and exchanging opinions, and (2) fostering a sense of individual responsibility in cooperative learning. The implications of these findings are that teachers can implement the jigsaw technique as a learning strategy to sharpen students’ reading comprehension by leveraging the aspects of collaborative discussion and individual responsibility inherent in the learning process.